Co-design of a multifaceted intervention to improve quality handover of medicine information at discharge from hospital - H. Laetitia Hattingh; Matt Percival; Kate Johnston; Georgia Tobiano; Hayley Hirsch; Carl de Wet; Salim Memon; Mark A. Morgan; Rachael Raleigh; Noela Baglot; Brigid M. Gillespie (BMC Health Services Research)
Abstract Background Timely and accurate discharge medicine information is essential for primary care clinicians, including general practitioners and community pharmacists, to provide safe and effective post-discharge care. Inadequate handover of discharge medicines poses risks of medication-related harm, compromising patient safety and leads to hospital readmissions. This study aimed to develop a multifaceted intervention targeting older patients (>65 years) to enhance medicine handover at hospital discharge. Methods Following an initial consensus-building workshop, a structured five-step co-design process was implemented. Step 1 involved workshops and interviews with hospital clinicians, hospital leadership, primary care providers, and consumers experienced in discharge medicine handover. Stakeholder input in Step 2 refined intervention components and developed training materials. Step 3 obtained endorsement from health service decision makers and governance approvals. Step 4 included pharmacist upskilling, end-user testing, and feedback collection. Step 5 finalised intervention components and constructed a Logic Model. Results Seventy-eight stakeholders participated in workshops and interviews from August to November 2023. Four key medicine handover objectives for older patients emerged, which were operationalised into intervention recommendations over a five-month period (December 2023-April 2024). Component 1 empowered patients to query clinicians about their medications via a dedicated website with a question builder and evidence-based resources. Component 2 involved training doctors to document reasons for medicine changes in patient records. Component 3 implemented patient risk stratification to guide tailored strategies for communication to primary care clinicians. Component 4 focused on discharge reconciliation planning by unit pharmacists in collaboration with physicians. End-user testing yielded positive feedback. Conclusions A co-designed multifaceted intervention was developed to enhance medicine handover during hospital discharge. The intervention will undergo feasibility testing to assess its impact on reducing medication-related harm and hospital readmissions.